Penerapan Discovery Learning untuk Meningkatkan Hasil Belajar Siswa Kelas X.3 UPT SMA Negeri 6 Maros pada Mata Pelajaran Bahasa Inggris - Liza Ain Azisiyah; Kiki Patmala; Fasikul Ikhsan; Abdul Rahman Rahim (Lembaga Pengembangan Kinerja Dosen, 2024)
The purpose of this research is to determine the application of the Discovery Learning learning model with the research subjects of students in class X.3 UPT SMA Negeri 6 Maros, totaling 28 students. The type of research used in this research is classroom action research (PTK). This research takes the form of a cyclical assessment process consisting of 4 stages, namely planning, implementation, observation and reflection. Data regarding student activities during the teaching and learning process and the teacher's ability to manage learning were collected using observation sheets. And data regarding student learning outcomes is collected by giving a learning outcomes test at the end of each cycle. The results of observations in the first cycle of learning results by applying the Discovery Learning learning model showed that learning completion reached 14.3% or 4 students out of 28 students had completed learning. The results of observations in cycle II of completeness of learning outcomes reached 35.8% or 10 students out of 28 students had completed their studies. From the results of the actions in cycle I and cycle II, it was concluded that the application of the Discovery Learning learning model could improve student learning outcomes at UPT SMA Negeri 6 Maros for the 2022/2023 academic year.